Dampak Mata Kuliah Metodologi Penelitian terhadap Persepsi dan Kesiapan Penelitian Mahasiswa Pendidikan Ekonomi UNESA: Pendekatan Fenomenologi Kualitatif - Fatih Allam Misbah; Albrian Fiky Prakoso; Riza Yonisa Kurniawan (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This study aims to explore the impact of a research methodology course on the perceptions and readiness of Economic Education students at UNESA using a qualitative phenomenological approach. The main issues addressed include students’ anxiety, confusion, and preparedness in conducting research, particularly thesis writing. Data were collected through in-depth interviews with participants who had completed the course and were undergoing thesis preparation. Results indicate that the course significantly improved students’ perceptions, transforming anxiety into confidence and motivation. Research readiness increased through structured learning, hands-on practice, intensive lecturer guidance, and peer support. Key challenges included difficulties in finding relevant journals, data processing, and time management, which were addressed through collaborative strategies and technology utilization. The course materials were deemed relevant to Economic Education research needs, though contextual adjustments to case studies were recommended. The study suggests curriculum development based on real-world cases, enhanced support facilities, and continuous mentoring to optimize student preparedness. These findings contribute to designing effective and responsive research methodology learning strategies in higher education.